Workshop Pengisian Formulir Etik Penelitian Pada Hewan Coba Di Fakultas Kedokteran Universitas Baiturrahmah - Dessy Abdullah; Mutiara anissa; sri nani jelmila (Stikes Syedza Saintika Padang, 2021)
Controversy over the use of test animals is common. Researchers sometimes say the test animal is just an animal, so researchers forget that animals also have the right not to feel pain and be free from torture. For the creation of an ideal treatment for test animals, researchers should pay attention to the ethics of surgery and follow the ethical guidelines of health research. This study aims to find out the picture of the application of ethical forms on animals at the Faculty of Animal Investigation Baiturrahmah University. The research method used is descriptive. The study was conducted by baiturrahamh medical students in Padang city with 80 people. The study measuring tool uses a google form questionnaire—processing data with excel. The results obtained the most answer the example of treatment that meets freedom from Hunger and thirst is to provide appropriate feed to animals try as many as 72 people (90%), most answers about the placement of animals try in a room that is light enough, large cages accordingly so that animals try to be comfortable is a treatment is freedom from discomfort that is 70 people (87.5%) and most answer about the three basic principles of ethical research in animals try is respect. That is 54 people (67.5%). The conclusion was obtained that the example of treatment that meets freedom from Hunger and thirst is to provide appropriate feed to the animal try, the placement of the animal tries in a room that is light enough, large cages accordingly so that animals try to be comfortable is a treatment is freedom from discomfort and about the three basic principles of ethical research in animals try is respect